Cross transferability, diversity analysis and tagging of MYMV resistance in mungbean using RGH markers - Narasimhan, A.; Patil, B. R.; Jangid, V. K.; Hemareddy, H. B.; Naik, P.M.; Kotagi, K.S.; Datta, S. (The Indian Journal of Genetics and Plant Breeding, 2016)
Mungbean and urdbean suffer from paucity of genetic markers associated with MYMV disease. As an alternative option RGHs were tested for transferability in 13 and 12 genotypes of mungbean and urdbean, respectively. Fiftyfive RGH markers from cowpea, chickpea and Medicago exhibited a transferability of 58.2%, which collectively yielded 51 alleles with an average of 1.59 alleles per locus. PIC of individual loci ranged from 0.19 to 0.64. Phylogenetic tree formed two different clusters of mungbean and urdbean with six sub clusters. Two putative markers identified and high level of transferability indicated its importance for marker-assisted breeding.